Registration of 'ANPELON' Winter Forage Triticale. Issue 3 (18th July 2014) - Lozano-del Río, A. J.; Lozano-Cavazos, C. J.; Ibarra-Jiménez, L.; de la Cruz-Lázaro, E.; Ammar, K.; Mergoum, M.; Pfeiffer, W. H.; Zamora-Villa, V. M.; Colín-Rico, M.; García-Martínez, J. E.; Lozano-Cavazos, E. A.; Gordillo-Melgoza, F. A.; et al.
Abstract : 'ANPELON' (Reg. No. 2640‐TCL‐014‐010313, Mexico; Reg. No. CV‐32, PI 669388) winter triticale (× Triticosecale Wittm.) was selected from the heterogeneous population URSS 3310, sent to Universidad Autónoma Agraria Antonio Narro (UAAAN) by the International Maize and Wheat Improvement Center (CIMMYT), Mexico, and registered and released as a forage cultivar in Mexico by the UAAAN and the National Seed Inspection and Certification Service (SNICS) in 2012. ANPELON was released because of its biomass production, regrowth capacity, awnless spikes, and nutritive value. The primary selection was based on agronomic characteristics and resistance to stem rust (caused by Puccinia graminis Pers. f. sp. tritici Eriks. & Henn) and leaf rust (caused by P. recondita Rob. ex Desm. f. sp. tritici ) and subsequently, on forage and nutritional characteristics. The reference cultivar was 'TCLF‐AN‐31' winter triticale (Reg. No. CV‐25, PI 620762), released as a forage cultivar by the UAAAN in 1992 (Reg. No. TCL‐07‐080592, Mexico).